2019
DOI: 10.3390/su11071831
|View full text |Cite
|
Sign up to set email alerts
|

Variation of Greenhouse Gases Fluxes and Soil Properties with Addition of Biochar from Farm-Wastes in Volcanic and Non-Volcanic Soils

Abstract: The decomposition of organic wastes contributes to greenhouse gas (GHG) emissions and global warming. This study evaluated the effect of biochar (BC) produced from different farm wastes (chicken, pig and cow manures) on greenhouse gas emissions and soil chemical and biological properties in different grassland soils (volcanic and non-volcanic soils). A 288-day laboratory experiment was carried out, monitoring CO2, N2O and CH4 emissions and evaluating total C, soil pH, microbial biomass and enzymatic activity i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 45 publications
1
13
0
Order By: Relevance
“…In this study, the C contents of RBs, NSBs, and LBs exceeded 70%, which were significantly higher than those of most reported biochars, and those of the NSB were similar to those of the previously reported pecan shell biochars [16,31,38,61]. Therefore, when compared to other biochars, RBs, NSBs, and LBs may be more beneficial for improving soil organic matter content [62,63]. The C/N ratio is a key factor that can affect the soil nutrient cycle and metabolic processes [64].…”
Section: Elemental Analysissupporting
confidence: 84%
“…In this study, the C contents of RBs, NSBs, and LBs exceeded 70%, which were significantly higher than those of most reported biochars, and those of the NSB were similar to those of the previously reported pecan shell biochars [16,31,38,61]. Therefore, when compared to other biochars, RBs, NSBs, and LBs may be more beneficial for improving soil organic matter content [62,63]. The C/N ratio is a key factor that can affect the soil nutrient cycle and metabolic processes [64].…”
Section: Elemental Analysissupporting
confidence: 84%
“…and Lin et al (2015) found that maximum CO2 and N2O emissions occurred in high soil C: N ratios (> 10). Crop residues increase soil C: N ratio in NT soils as compared to CT, also enhance microbial activities, and alternatively increase GHGs emissions (Mosier et al, 2006a;Muñoz et al, 2019).…”
Section: (Aii Bii Cii))mentioning
confidence: 99%
“…Application of animal manure and compost (under high soil C: N ratio) increased the denitrification process, which ultimately increased the availability of soil N contents, which favors the N 2 O emissions (Charles et al, 2017). On the other hand, biochar application may also enhances soil C: N ratio, also improves microbial activities, and increases GHGs emissions (Muñoz et al, 2019). Most of the research studies that were comprised in this meta-analysis study did not account the changes of soil C: N ratio with animal manure and biochar amendments, so might be due to this, we found variation in the results.…”
Section: Soil C: N Ratiomentioning
confidence: 99%